Barriers and Solutions to Advancing Emergency Medicine Simulation–based Research: A Call to Action. (27th November 2019) - Bentley, Suzanne; Stapleton, Stephanie N.; Moschella, Phillip C.; Ray, Jessica M.; Zucker, Shana M.; Hernandez, Jessica; Rosenman, Elizabeth D.; Wong, Ambrose H.
Abstract: Simulation technology has successfully improved patient safety and care quality through training and assessment of individuals, teams, and health care systems. Emergency medicine (EM) continues to be a leader and pioneer of simulation, including administration of simulation‐based fellowships and training programs. However, EM simulation–based research has been limited by low rates of publication and poor methodologic rigor. The Society for Academic Emergency Medicine (SAEM) Simulation Academy is leading efforts to improve the quality of scholarship generated by the EM simulation community and to foster successful research careers for future generations of EM simulationists. Through a needs assessment survey of our membership and a year‐long consensus‐based approach, we identified two main clusters of barriers to simulation‐based research: lack of protected time and dedicated resources and limited training and mentorship. As a result, we generated four position statements with implications for education, training, and research in EM simulation and as a call to action for the academic EM community. Recommendations include expansion of funding opportunities for simulation‐based research, creation of multi‐institutional simulation collaboratives, and development of mentorship and training pathways that promote rigor in design and methodology within EM simulation scholarship.